Relationship Between Carbon- and Oxygen-Based Primary Productivity in the Arctic Ocean, Svalbard Archipelago - Sanz-Martín, Marina; Vernet, María; Cape, Mattias R.; Mesa, Elena; Delgado-Huertas, Antonio; Reigstad, Marit; Wassmann, Paul; Duarte, Carlos M. (Frontiers in Marine Science, 2019)
Phytoplankton contribute half of the primary production in the biosphere and are the major source of energy for the Arctic Ocean ecosystem. While primary production measurements are therefore fundamental to our understanding of marine biogeochemical cycling, the extent to which current methods provide a definitive estimate of this process remains uncertain given differences in their underlying approaches and assumptions. This is especially the case in the Arctic Ocean, a region of the planet undergoing rapid evolution as a result of climate change, yet where primary production measurements are sparse. In this study, we compared three common methods for estimating primary production in the European Arctic Ocean: 1) production of 18O-labeled oxygen (GPP-18O), 2) changes in dissolved oxygen (GPP-DO) and 3) incorporation rates of 14C-labelled carbon into particulate organic carbon (14C-POC) and into total organic carbon (14C-TOC, the sum of dissolved and particulate organic carbon). Results show that primary production rates derived using oxygen methods showed good agreement across season and were strongly positively correlated. While also strongly correlated, higher scatter associated with seasonal changes was observed between 14C-POC and 14C-TOC. The 14C-TOC-derived rates were, on average, approximately 50 % of the oxygen-based estimates. However, the relationship between these estimates changed seasonally. In May, during a spring bloom of Phaeocystis sp., 14C-TOC was 52 % and 50 % of GPP-DO and GPP-18O respectively, while in August, during post-bloom conditions dominated by flagellates, 14C-TOC was 125 % of GPP-DO and 14C-TOC was 175 % of GPP-18O. Varying relationship between C and O rates may be the result of varying importance of respiration, where C-based rates estimate Net Primary Production (NPP) and O-based rates estimate Gross Primary Production (GPP).However, uncertainty remains in this comparison, given differing assumptions of the methods and the photosynthetic quotients.The median O:C ratio of 4.75 in May is within the range of that observed for other regions of the world’s ocean. However, the median O:C ratio for August is < 1, lower than in any other reported region. Our results suggest further research is needed to estimate O:C in Arctic waters, and at different times of the seasonal cycle.